Free vascularized medial femoral condyle corticoperiosteal flap with non-vascularized iliac crest graft for the treatment of recalcitrant clavicle non-union. Issue 7 (July 2020) - Jaloux, Charlotte; Bettex, Quentin; Levadoux, Michel; Cerlier, Alexandre; Iniesta, Aurélie; Legre, Régis; Mayoly, Alice; Gay, André
Summary: Clavicle non-union is a challenging problem. Open reduction with internal fixation and autologous bone grafting is usually the first line treatment. In case of failure, the medial femoral condyle corticoperiosteal flap in association with a non-vascularized bone graft is one of the therapeutic options, which is well adapted to the clavicle anatomical characteristics. We performed a retrospective study of all patients treated with this technique in our department. Between 2014 and 2017, five patients with recalcitrant post traumatic clavicle non-unions received this surgical treatment. The average nonunion time period was 50.2 month (range 10 to 108 months), and the mean defect length was 3.4 cm (between 2 and 5 cm), defects were all located in the medial third of the clavicle Three patients achieved full consolidation with an average time of consolidation of 8, 7 months (range 6 to12 months). Patients with radiological consolidation had better functional improvement and pain reduction with an average DASH score improved from 53, 6 before surgery to 19, 6 after consolidation (at the last follow up visit). There was one donor site complications (hematoma). The medial femoral condyle corticoperiosteal flap with non-vascularized iliac crest graft is a good option for the management of recalcitrant clavicle non-union, especially when the bone defect is small.